Preparation and characterization of MnIIMnIII complexes with relevance to class Ib ribonucleotide reductases - Mc Donald, Aidan (My University, 2024)
The Mn2 complex [MnII 2(TPDP)(O2CPh)2](BPh4) (1, TPDP = 1,3-bis(bis(pyridin-2-ylmethyl)amino)propan-2-ol, Ph =phenyl) was prepared and subsequently characterized via single-crystal X-ray diffraction, X-ray absorption, electronic absorption, and infrared spectroscopies, and mass spectrometry. 1 was prepared in order to explore its properties as a structural and functional mimic of class Ib ribonucleotide reductases (RNRs). 1 reacted with superoxide anion (O2 •– ) to generate a peroxido-MnIIMnIII complex, 2. The electronic absorption and electron paramagnetic resonance (EPR) spectra of 2 were similar to previously published peroxido-MnIIMnIII species. Furthermore, X-ray near edge absorption structure (XANES) studies indicated the conversion of a MnII 2 core in 1 to a MnIIMnIII state in 2. Treatment of 2 with para-toluenesulfonic acid (p-TsOH) resulted in the conversion to a new MnIIMnIII species, 3, rather than causing O—O bond scission, as previously encountered. 3 was characterized using electronic absorption, EPR, and X-ray absorption spectroscopies. Unlike other reported peroxidoMnIIMnIII species, 3 was capable of oxidative O—H activation, mirroring the generation of tyrosyl radical in class Ib RNRs, however without accessing the MnIIIMnIV state.
Keywords: Mn2 complex; Bioinorganic, Dimanganese cluster, Ribonucleotide reductase, Dioxygen activation, electron paramagnetic resonance